Immobilization of uranium in cristobalite ceramic through adsorption on mesoporous SBA-15 and further sintering process. Issue 5 (May 2020) - Ding, Yi; Xian, Qiang; Jiang, Zhengdi; Chen, Li; Xiong, Tianheng; He, Xinmiao; Yang, Wenping; Dan, Hui; Duan, Tao
Graphical abstract: Highlights: Adsorption and sintering route was employed to immobilize U. Mesoporous SBA-15 platelets with short pore length were used to adsorb U. SBA-15 adsorbed U can be transformed into stable cristobalite waste forms. Stable cristobalite waste forms were formed after sintering at 1100−1400 °C for 6 h. The obtained waste forms exhibit good aqueous durability (∼10 −4 g m -2 d -1 ). Abstract: The development of an adsorbent which can be easily transformed into stable ceramic waste forms through a simple route is necessary for the treatment of the radioactive wastewater. Herein, we report on the immobilization of uranium in cristobalite ceramic through adsorption on mesoporous SBA-15 and further sintering process. The mesoporous SBA-15 with short pore length was synthesized and employed to remove uranium from aqueous solution. Subsequently, the SBA-15 with adsorbed U (U/SBA-15) was solidified by sintering. The effects of sintering temperature and U content on the structure, densification and aqueous durability of the obtained cristobalite ceramic waste forms were investigated. The results indicate that the U/SBA-15 can be transformed into stable cristobalite ceramic after sintering at 1100–1400 °C for 6 h. Furthermore, all the obtained cristobalite ceramic waste forms exhibit good aqueous durability (∼10 −4 g m -2 d -1 ). This work demonstrates a potential route and adsorbent to dispose the radioactive wastewater.